IDENTIFIKASI BAKTERI PENGHASIL AMILASE YANG BERASAL DARI TANAH TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH DI KOTA PADANG - -, Gusnayetty - (STKIP PGRI Sumbar, 2014)
Amylase is an enzyme that plays a role in hidrolysis starch into simple sugars. Various industries in Indonesia using amylase as a catalyst, as in the food industry amylase role in making foods, drinks, or liquid sugar and non-food industries amylase used in the textile, paper and detergent. Some types of bacteria such as Bacillus sp. and Aspergillus sp. a group that has a great ability to produce amylase. Amylase producing bacteria have been isolated from soil landfills (TPA) in the city of Padang, but identification has not been done. This research aims to determine the amylase producing bacteria from the ground landfills (TPA) in the city of Padang. The research was conducted from July to August 2014 in the laboratory Kopertis Region X and in the Balai Penyidikan and Pengujian Veteriner Regional II Bukit Tinggi. This research uses descriptive method. The results of bacterial identification of isolates T2.4, T3.7, and T4.5 includes identification macroscopic and microscopic morphology and biochemical identification of the isolates showed that the T2.4 is a bacteria of the genus Enterobacter, whereas isolates T3.7 and T4.5 is bacteria of the genus Bacillus.